Collective Memory Distortion and the Quest for the Historical Jesus - Crook, Zeba A. (Journal for the study of the historical Jesus, 2013)
Memory theory is being used, if not explicitly to buttress the reliability of the Gospel portraits of Jesus, to do so implicitly by shifting the search away from the ipsissima verba Jesu towards the memory of Jesus. Rather than argue about what Jesus did or did not say—the reliability wars—some scholars now sidestep the issue by arguing that memory is inherently reliable in a broad or general way. Thus, the Gospels are reliable not at the level of detail, but at the level of broad memory, impact, or gist. In this article I argue that such optimism can only come by selectively quoting the troubling work of memory theorists, and by ignoring the full implications of memory theory.